115k views
2 votes
2(x+3)=5(x-1)+6. show all steps please.

User Thaisa
by
4.4k points

1 Answer

6 votes

Answer: x=5/3

Explanation:

For this problem, you want to solve for x. You first distribute, get all like terms to one side, and then sovle for x.

2(x+3)=5(x-1)+6

2x+6=5x-5+6. (combine like terms)

2x+6=5x+1 (move all like terms to one side)

5=3x (divide to solve for x)

x=5/3

User Epharion
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.